Harmonization and Ambiguity in Regulations for Physicians with Family Medicine Competence Post-Law No. 17 of 2023 - Katon, Danar Wahyu Giwang; Ayuningtyas, Dumilah; Junadi, Purnawan; Sulistiadi, Wahyu; Pattiselanno, Roberth J.; Fitria, Fitria; Alfiani, Ika Fitri (UI Scholars Hub, 2026)
Strengthening primary care services in Indonesia requires that community health centers, namely Pusat Kesehatan Masyarakat (Puskesmas), involve medical personnel with family medicine competence. However, the fulfillment of physicians with this competence, especially Primary Care Family Medicine Specialists or Spesialis Kedokteran Keluarga Layanan Primer (Sp.KKLP), still face significant obstacles. This qualitative research uses the integrated Easton's System Model and Buse's Policy Framework to analyze the dynamics of this policy. The findings reveal a gap between the strong legal foundation and weak implementation mechanisms on the ground. First, there is ambiguity in terminology and lack of harmonization among regulations, especially concerning the Sp.KKLP nomenclature, which creates confusion in terms of legal status and professional recognition. Second, an implementation gap (policy–practice gap) exists because the central government has not yet issued technical derivative regulations (technical guidelines, compensation mechanisms). Furthermore, the decentralization of authority and limited regional budgets impede the equitable placement of the Sp.KKLP. The success of the policy relies heavily on the synergy among the Ministry of Health, Health Council, Family Medicine Collegium, educational institutions such as Program Pendidikan Dokter Spesialis (PPDS) and Recognition of Prior Learning (RPL), and professional organizations such as Pengurus Besar Ikatan Dokter Indonesia (PB IDI). Recommendations include the development of technical implementation regulations, clarification of the Sp.KKLP definition, and establishment of inclusive pathways for competence enhancement such as PPDS and RPL.